Impact of Real Earnings Management on Profitability and Firm Value: A Study of Manufacturing Companies in India - Naseer Al-Habsi (one million dreams corporation, 2025)
This study aims to analyze the effect of real earnings management (REM) practices on profitability and firm value. The study uses secondary data from 250 manufacturing companies listed on the Bombay Stock Exchange (BSE) Top 500 during the period 2017–2021. The research design used is correlational with a multiple linear regression approach. The analysis results show that the intensity of REM has a significant negative effect on firm performance as measured by Return on Assets (ROA) and on firm value as proxied by Tobin's Q in the following year. These findings indicate that REM practices not only harm long-term profitability but also erode firm value. This study strengthens empirical evidence regarding the negative consequences of REM and provides implications for management and regulators in order to improve the quality of financial reporting and protect stakeholder interests.